1989
DOI: 10.1111/j.1432-1033.1989.tb15235.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth control strength and active site of yeast plasma membrane ATPase studied by site‐directed mutagenesis

Abstract: Several amino acids which are conserved in cation-pumping ATPases with phosphorylated intermediate have been mutagenized in the yeast plasma membrane H +-ATPase. The mutant genes have been selectively expressed in a yeast strain where the wild-type ATPase is only expressed in galactose nicdium. A scrics of mutants with decreasing levels of activity demonstrates that the ATPase is rate-limiting for growth and that decreased ATPase activity correlates with decreased intracellular pH. Enzymatic and transport stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 50 publications
2
80
0
Order By: Relevance
“…The role of this domain was conis the first among the AHA family members to have a clear and essential phenotype, and similar observations firmed by several studies, which showed that truncation or displacement of the C terminus of plant H ϩ -ATPases with other single AHA knockouts have not been seen (Young et al 2001). yielded a constitutively activated enzyme when expressed in yeast (Portillo and Serrano 1989;Palmgren et al On the basis of previous work describing AHA3 localization in companion cells, we predicted a role for this 1990; Portillo et al 1991;Palmgren and Christensen 1993;Regenberg et al 1995). Activation in vivo is initigene in phloem loading, and consequently that an AHA3 knockout plant would be deficient in this process.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The role of this domain was conis the first among the AHA family members to have a clear and essential phenotype, and similar observations firmed by several studies, which showed that truncation or displacement of the C terminus of plant H ϩ -ATPases with other single AHA knockouts have not been seen (Young et al 2001). yielded a constitutively activated enzyme when expressed in yeast (Portillo and Serrano 1989;Palmgren et al On the basis of previous work describing AHA3 localization in companion cells, we predicted a role for this 1990; Portillo et al 1991;Palmgren and Christensen 1993;Regenberg et al 1995). Activation in vivo is initigene in phloem loading, and consequently that an AHA3 knockout plant would be deficient in this process.…”
Section: Discussionmentioning
confidence: 59%
“…The most likely role of AHA3 in growing microspores is the mutants mad2 and mad3 are defective during pollen mitosis I, which occurs after reabsorption of the vacuoles control of nutrient uptake. As their dependence on the surrounding sporophytic tissues (tapetum) for nourishin vacuolated microspores (Grini et al 1999); mad1 is defective during pollen mitosis II (Grini et al 1999), ment decreases, early vauolated microspores rely increasingly on the activity of the plasma membrane H ϩ -ATPase as is ttd38 (Procissi et al 2001); mad4 is defective in pollen tube elongation (Grini et al 1999); and raringfor the transport of nutrients. If this protein is nonfunctional, the microspores starve and die.…”
Section: Discussionmentioning
confidence: 99%
“…The black boxes are regions which show more than 15% mean identity in pairwise comparisons of sequence segments of skeletal Ca2+-ATPase, sheep Na'+/K+-ATPase, yeast H+-ATPase and E. coli K+-ATPase. The circled residues are those from S. cerevisiae PMAI, which after mutation lead to vanadate resistance of ATPase activity [7,22,23,301 bition patterns exhibited by vanadate, even though the molecular site of action of this inhibitor in the phosphorylation site is likely to be identical. In this study we confirm that in yeast H +-ATPase, vanadate is a typical non-competitive inhibitor with a Ki of 4.3 pM.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma-membrane H +-ATPase is essential [4] and rate limiting for growth, about 30% of the wildtype activity being the threshold required for normal growth [23,311. Since the K, values for the mutant enzyme are strongly modified within the physiological range of cellular pH and ATP, VjK, seems to be a more appropriate index to measure ATPase efficiency than the specific activity.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast the plasma membrane H+-ATPase exerts a strong control on growth rate [58]. The metabolic role of this Hf-ATPase, however, is quite different, not lying on the main route of free-energy transduction but serving to control the intracellular pH.…”
Section: Control By Free-energy Metabolismmentioning
confidence: 99%